Development of Sustainable Rural Tourism - Sandra Kantar; Kristina Svržnjak (DETUROPE)
This paper presents a sociological view of possibilities for the development of sustainable rural tourism in Koprivnica-Krizevci county, which is located in the north-western part of Croatia. The possibilities for developing rural tourism within the concept of sustainable development have been researched through qualitative empirical research interview method. Research subjects were the owners of tourist farms, decision makers, experts and other stakeholders in the tourism development. Rural tourism represents an alternative to maritime tourism and is relatively undeveloped but important in terms of development of rural areas and family farms. This paper enables an insight into an integrated sustainability of rural tourism which consists of four dimensions: biologicalecological, economic, socio-cultural and political sustainability. In conclusion, integral sustainability in rural tourism is not achieved in all dimensions. Therefore, rural tourism could be a strategy for sustainable development for rural areas and also could be a tool for product differentiation for area that are at stagnation stage.